2013
DOI: 10.1242/jcs.123802
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a radial SNARE super-complex mediating neurotransmitter release at the Drosophila neuromuscular junction

Abstract: SummaryThe SNARE proteins VAMP/synaptobrevin, SNAP-25 and syntaxin are core components of the apparatus that mediates neurotransmitter release. They form a heterotrimeric complex, and an undetermined number of SNARE complexes assemble to form a super-complex. Here, we present a radial model of this nanomachine. Experiments performed with botulinum neurotoxins led to the identification of one arginine residue in SNAP-25 and one aspartate residue in syntaxin (R206 and D253 in Drosophila melanogaster). These resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 70 publications
(94 reference statements)
1
22
0
Order By: Relevance
“…SNAP-25 1–197 may persist for long periods of times after generation by BoNT/A (Keller et al., 1999; Foran et al, 2003; Meunier et al, 2003). Taken together, these data are consistent with the suggestion that SNAP-25 1–197 may contribute significantly to the long duration of action of BoNT/A by acting as a dominant negative component of a neuroexocytosis nanomachine, consisting of several SNARE complexes arranged radially whose assembly/function is critically dependent on an intact SNAP-25 C-terminus (Megighian et al, 2013; Pantano and Montecucco, 2014). Also the long duration of action of BoNT/C in human and mice is likely to be due to an inhibitory action of a long-living SNAP-25 1–198 fragment.…”
Section: Biologysupporting
confidence: 89%
See 1 more Smart Citation
“…SNAP-25 1–197 may persist for long periods of times after generation by BoNT/A (Keller et al., 1999; Foran et al, 2003; Meunier et al, 2003). Taken together, these data are consistent with the suggestion that SNAP-25 1–197 may contribute significantly to the long duration of action of BoNT/A by acting as a dominant negative component of a neuroexocytosis nanomachine, consisting of several SNARE complexes arranged radially whose assembly/function is critically dependent on an intact SNAP-25 C-terminus (Megighian et al, 2013; Pantano and Montecucco, 2014). Also the long duration of action of BoNT/C in human and mice is likely to be due to an inhibitory action of a long-living SNAP-25 1–198 fragment.…”
Section: Biologysupporting
confidence: 89%
“…These results led to the suggestion that SNAP-25 1–197 acts as a dominant negative factor in the function of a multimeric radial super-SNARE complex because the C-terminal segment is necessary for protein-protein interactions underpinning the formation of a radial SNARE super-complex (Montecucco et al, 2005; Pantano and Montecucco, 2014). Electron microscopy data indicate that multimeric SNARE supercomplexes exist in the CNS (Rickman et al, 2005), and indirect evidence for the existence of an octameric neuroexocytosis radial nanomachine have been obtained (Megighian et al, 2013). A variety of experimental approaches have been used to estimate the number of SNARE complexes forming the nanomachine that mediates vesicle-target membrane fusion and a range of figures have been produced (reviewed in Pantano and Montecucco, 2014).…”
Section: Biologymentioning
confidence: 99%
“…The organization of SNAREs into clusters may be functional as reservoirs of SNARE molecules, allowing for rapid interactions with their cognate partners (Rickman et al, 2010; Bar-On et al, 2012). Alternatively, the multimerization of the SNARE complex was also reported to be mediated by the interaction between the SNARE motifs of SNAP25 and syntaxin via forming an ionic couple to link neighboring SNARE complexes, thus leading to a radial organization (Megighian et al, 2013). EPR and fluorescence studies showed that SNARE proteins could self-assemble through the interaction between TMDs, and the oligomeric structure could serve as a scaffolding for the formation of the trans-SNARE complex which leads to the formation of a supramolecular structure containing at least three copies of SNARE complexes (Lu et al, 2008).…”
Section: Snare-snare Interactions In Exocytosismentioning
confidence: 99%
“…Null mutations in Snap-25 have relatively normal neurotransmitter release at third instar NMJs, with the similar SNAP-24 protein proposed to compensate for the loss (Vilinsky et al 2002). These redundancy issues confound robust structure-function approaches that have been applied to other proteins like Synaptotagmin, although there have been some efforts in the field to examine hypomorphic mutations of the SNARE proteins in Drosophila Wu et al 1999;Stewart et al 2000;Rao et al 2001b;Bykhovskaia et al 2013;Megighian et al 2013;Demill et al 2014). Although the requirement for the SNARE complex in fusion is well accepted, there are still numerous questions.…”
Section: Snare-mediated Fusionmentioning
confidence: 99%